Translation and psychometric evaluation of the Swedish versions of the Nuss Questionnaire modified for Adults and the Single Step Questionnaire - Louise Norlander; Jan Karlsson; Agneta Anderzén-Carlsson; Mårten Vidlund; Mats Dreifaldt; Jesper Andreasson; Ann-Sofie Sundqvist (SpringerOpen, 2021)
Abstract Background Pectus excavatum (PE) is the most common congenital chest wall deformity. Most individuals with PE suffer from psychosocial problems, with low self-esteem and poor body image. Correctional surgery for PE is available, the most widely used is the Nuss procedure. The Nuss procedure has previously been reported to improve self-esteem, body image and health-related quality of life (HRQoL). To assess HRQoL among individuals with PE, the Nuss Questionnaire modified for Adults (NQ-mA) and Single Step Questionnaire (SSQ) has been developed. The aim of the current study was to translate and culturally adapt NQ-mA and SSQ to fit a Swedish context, and to evaluate the psychometric properties, and validate the culturally adapted versions. Methods Individuals who had undergone the Nuss procedure for pectus excavatum were invited to participate in a multicentre study with cross-sectional design. HRQoL was assessed by NQ-mA, SSQ and RAND-36. Psychometric properties for NQ-mA and SSQ were evaluated by content validity index and construct validity (exploratory factor analysis, confirmatory factor analysis, and inter-scale correlations). Known-groups validity, as well as floor and ceiling effects, were evaluated. Internal consistency reliability was examined using Cronbach's alpha. Results In total 236 individuals participated in the study. Content validity index for NQ-mA showed satisfactory results, except for two items. Factor analysis for NQ-mA suggested a two-factor model, with exclusion of two items. Subscales correlated adequately with RAND-36's domains. Known-groups validity for NQ-mA demonstrated high sensitivity for between-group differences. Ceiling effects were present in several items. Cronbach's alpha for NQ-mA was .89. Confirmatory factor analysis for SSQ resulted in a three-factor model, with exclusion of five items. However, this model was shown to be unstable through further exploratory factor analysis testing, and no further psychometric tests were conducted for SSQ. Conclusion The 10-item Swedish version of NQ-mA was shown to be valid for research and clinical assessment of HRQoL in individuals with pectus excavatum. The Swedish version of SSQ requires revision of items before further validation can be performed.